The Influence of Emotional Intelligence, Work Discipline on Teacher Performance at SDN Jatiwaringin VIII - Framsiska, Meliana; Sudari, Suci Ayu; Rachmawati, Dwi (Lead Journal of Economy and Administration, 2024)
In the era of growing modernization, human resource management has a key role in the running of an organization. Teachers have a fundamental role in education, teachers spearhead the success of an education. Education is an important factor that determines the growth and survival of a nation. Teacher performance is the key to the success of the quality of the nation's generation, therefore every party in the world of education is always trying to find ways to improve teacher performance in order to create professional teachers. This study aims to determine the significant effect of emotional intelligence and work discipline on teacher performance at Jatiwaringin VIII Elementary School. This type of research is quantitative method research. For data collection using questionnaire techniques as a research instrument. The sampling technique used was saturated sampling with a sample size of 30 respondents. Data analysis using multiple linear regression analysis using the help of the SPSS software program. The results of hypothesis testing and multiple linear regression indicate that emotional intelligence and work discipline have a positive and significant impact on teacher performance at SDN Jatiwaringin VIII. Emotional intelligence and work discipline contribute 52.3% to teacher performance. SDN Jatiwaringin VIII can improve teacher performance by conducting evaluations related to understanding and applying the importance of emotional intelligence and work discipline.